MINI REVIEW BIOMARKERS AS EARLY DETECTION TOOL FOR SILICA DUST EXPOSURE-INDUCED HEALTH PROBLEMS - Kusmiyati Kusmiyati (INTERNATIONAL JOURNAL OF NURSING AND MIDWIFERY SCIENCE (IJNMS), 2019)
The silica dust is widely distributed on earth’s surface resulting from various activities. This mineral may result in lung damage initially presenting changes of many compounds in biological systems. Silica exposure on lung tissues triggers reactive oxygen species (ROS) production, influences endogenous antioxidant enzymes (superoxide dismutase, catalase and glutathione peroxidase), and release of inflammatory mediators (IL-1, IL-6, TNF-α). These biomarkers are developed as marker of silica exposure effect in the body. It is concluded that development of biomarkers is warranted for early detection of silica exposure-induced health problems in order to prevent its progression into serious diseases.